DAUR VOLUME OPTIMAL JATI DI HUTAN RAKYAT (STUDI KASUS DI DESA GIRIKARTO, KECAMATAN PANGGANG, KABUPATEN GUNUNG KIDUL - Suhartati, Tatik; Pebriansyah (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2021)
The aim of this research is to define rotation of optimal volume production of teak private smallholder forest. Sample of trees were taken by using purposive sampling method in cutting activity area. Seventy trees have choosen by diameter distribution, healthy and straigh stem. Every sample trees were measured with stem analysis method. Rotation of maximum volume production define by growth curve, mean annual increament (MAI) and current annual increament (CAI) curve. The result show that height youth stage begin 2 until 6 year, diameter youth stage begin 3 until 10 year, volume youth stage begin 4 until 25 year and rotation of maximum volume production is 25 year. Key words: Rotation of optimal volume production, Stem analysis, Growth curve